2016
DOI: 10.3389/fnhum.2016.00198
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Modulation of EEG Oscillations in High-Functioning Autism during a Motor Control Task

Abstract: Autism spectrum disorders (ASD) are thought to result in part from altered cortical excitatory-inhibitory balance; this pathophysiology may impact the generation of oscillations on electroencephalogram (EEG). We investigated premotor-parietal cortical physiology associated with praxis, which has strong theoretical and empirical associations with ASD symptomatology. Twenty five children with high-functioning ASD (HFA) and 33 controls performed a praxis task involving the pantomiming of tool use, while EEG was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 66 publications
2
41
0
Order By: Relevance
“…For example, infants at high-risk for ASD (36), as well as children (37, 38) and adults (39) with ASD have shown reduced power in the alpha-band frequencies. Studies examining task-related changes in alpha power in ASD have reported reduced alpha-band ERS, indicative of impaired suppression of task-irrelevant sensory information (5), reduced ERD during the preparation and execution of a motor control task (40), and increased frontal ERS, which may be related to the use of alternative strategies in ASD (41). Together, these findings suggest that ASD is associated with spontaneous and task-related differences in alpha power.…”
Section: Introductionmentioning
confidence: 99%
“…For example, infants at high-risk for ASD (36), as well as children (37, 38) and adults (39) with ASD have shown reduced power in the alpha-band frequencies. Studies examining task-related changes in alpha power in ASD have reported reduced alpha-band ERS, indicative of impaired suppression of task-irrelevant sensory information (5), reduced ERD during the preparation and execution of a motor control task (40), and increased frontal ERS, which may be related to the use of alternative strategies in ASD (41). Together, these findings suggest that ASD is associated with spontaneous and task-related differences in alpha power.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous report using EEG to study dyspraxia in children with ASD [Ewen et al, ], we observed decreased‐magnitude of regional task‐related power modulation (ERD) in alpha (7–13 Hz) and beta (18–23 Hz) bands. ASD‐related decreases in alpha ERD were specific to posterior (parietal) scalp regions, and decreases in beta ERD were specific to central scalp regions.…”
Section: Introductionmentioning
confidence: 67%
“…The EEG dataset analyzed here is the same data used in the ERD analysis [Ewen et al, ]. The experimental protocol and consenting process were approved by the Johns Hopkins Medicine Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suppression was, however, significantly weaker in the EPT than FT children, which may reflect reduced ability to engage the stimulus-relevant brain networks into active information processing. In a recent experiment, a group of autistic children showed reduced posterior alpha-band suppression in comparison with typically developing children while pantomiming tool use (Ewen et al, 2016). Decreased modulation of alpha oscillation was interpreted to indicate decreased task-related activation.…”
Section: Discussionmentioning
confidence: 99%